(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This study deals with the systematic investigation of cardiovascular problems in Covid-19 and multiple trauma patients hospitalized in special units, relying on radiology and analgesia stereotypes. Abnormal heart rhythm, which includes high heart rate, irregular heart rate and slow heart rate, can be one of the complications of Corona disease. Also, some of the drugs used for Corona may have side effects such as lowering the heart rate. For example, in one of the recent studies, after starting treatment with Remdesivir, some patients experienced a drop in heart rate. In this study, doctors used dopamine injections to stabilize the patient's heart rate during the 5-day period of Redemsivir treatment, and the patients' heart problems resolved spontaneously at the end of the treatment. Corona virus damages the heart in different ways. The formation of a blood clot is one of the serious complications of Corona, which in some cases leads to death. Its symptoms include severe pain in the chest (heart and lungs), as well as shortness of breath. If the infection caused by Corona disease is severe enough to damage the lungs, less oxygen reaches the heart, which can also reduce the delivery of nutrients to the heart. Therefore, the heart needs more oxygen. The lack of this oxygen and nutrients causes damage to the heart muscles, which is accompanied by pain. Among the other causes of heart pain during the Corona disease, we can mention the inflammation of the heart muscle (myocarditis) and the inner wall of the heart (pericarditis), which can be caused by viral infections. At first, scientists thought that this inflammation was caused by the direct attack of the Corona virus on the heart muscle, but with further research, it became clear that this condition is a result of the overreaction of the body's immune system to the infection caused by the virus and can Another reason for pain in the chest and heart and arrhythmia (irregular heartbeat).